The Development of Animal Personality - Ann V. Hedrick (Frontiers Research Topics, 2017)
Although the topic of animal personality has recently generated much interest, the role of development is little understood. This collection of papers deals with the development of animal personality. Topics include the roles of genetic effects, maternal effects, social partners, predation and parasitism risk, and environmental complexity in the development of personality, the effects of personality on survival, and the development of collective personality and movement as a driver of personality development. The organisms covered include insects, spiders, fishes, and birds. This volume illustrates the diversity of approaches that have shed light on the development of animal personality in the past several years.